Pengembangan E-LKPD Energi Dan Usahaberbasis React Untuk Meningkatkan Literasi Digital Siswa SMK - Abrila Zahrotus Sufia; Ahmad Khoiri; Siti Lailiyah (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
been fully accompanied by an increase in students’ digital literacy, especially at the vocational high school (SMK) level. This study aims to develop a digital student worksheet (E-LKPD) on Work and Energy based on the REACT (Relating, Experiencing, Applying, Cooperating, Transferring) model to enhance students’ digital literacy. The research employed the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The sample consisted of grade X AKL 3 students selected through purposive sampling. Research instruments included validation sheets, practicality questionnaires, tests, and digital literacy questionnaires. Validation results showed that media experts rated the product at 4.84 (96.84%) and subject matter experts at 4.45 (89%), both in the "very valid" category. Practicality tests by teachers and students yielded scores of 87.27% and 86.16%, respectively, categorized as "very practical." The paired sample t-test revealed a significant increase in concept understanding (sig. 0.001; N-Gain = 0.4599, medium category) and digital literacy (sig. 0.001; N-Gain = 0.7965, high category). Thus, the REACT-based E-LKPD is valid, practical, and effective in enhancing both conceptual understanding and digital literacy, contributing to 21st-century digital and contextual learning.